Translation and validation of oral health impact profile-49 questionnaire for use in hindi-speaking population - Neha Kwatra; Jasneet Sudan; Girish M Sogi; Sami Ahmed (Wolters Kluwer Medknow Publications, 2023)
Context: The subjective dimension of oral health has become a focus area for healthcare researchers in last decades. There has been an increase in scales measuring the self-perceived oral health outcomes. Oral health impact profile (OHIP-49) was developed in English, and for its use in Hindi-speaking population, translation and validation along with cross cultural adaptation are needed. Aim: To translate and validate OHIP-49 questionnaire for use in Hindi-speaking population. Settings and Design: Translation and validation of OHIP-49 questionnaire were carried out in a cross-sectional study conducted from January 2017 to October 2017 at a tertiary care centre. Methods and Material: A systematic random sample of 303 subjects reporting with orofacial pain was included in the study. The original English version OHIP-49 was initially translated and cross-culturally adapted to Hindi following WHO guidelines and then, subsequently validated. Statistical Analysis Used: The OHIP subscale measures were computed using Thurston's method. Internal consistency of the translated questionnaire was quantified in terms of Cronbach's alpha and average inter-item correlations for each domain. Results: The standardized overall Cronbach's alpha value derived from the correlation matrix was 0.88 (excellent). The average inter-item correlation coefficient was within the range of 0.3-0.5 for all the domains except for handicap domain. Conclusions: The OHIP-46-H questionnaire has an acceptable validity and reliability for use in Hindi-speaking population. It provides a possibility to narrate in details how frequently oral diseases affect the quality of life.